Athenian potters and painters, - Oakley, John Howard, 1949-; Palagia, Olga (Oxbow Books, 2009)
"This volume presents the proceedings of the second Athenian Potters and Painters conference, which was held at the American School of Classical Studies, Athens 2007. Together with the 1994 conference (Volume I, Oxbow 1997), these are the first of their kind - focusing purely on Athenian pottery and addressing key aspects of its study. The thirty-two papers contained here are the result not only of a large amount of new material but also the dynamic appearance of a younger generation of scholars dealing with the subject. Subject areas range from the study of the potters and painters themselves, to shape, subject matter, chronology, export, excavation pottery, context, and the influence of Athenian vases on pottery from other regions of the Mediterranean and vice versa. Three papers are in Greek."--Jacket